EFEKTIFITAS PELAKSANAAN PROGRAM BANTUAN OPERASIONAL SEKOLAH (BOS) DALAM MENINGKATKAN PRESTASI BELAJAR SISWA SMP NEGERI 1 BIROMARU DI KABUPATEN SIGI - Djafar, Djafar (Katalogis, 2017)
This study aims to determine the School Operational Grant (BOS) Program Implementation Efectivity in Improving Student Achievement SMP Negeri 1 Biromaru in Sigi Regency. Data were collected by observation, interview, questionnaire and documentation, were further analyzed by qualitative and quantitative descriptive analysis. This study intends to get a description and a picture of the BOS Program Implementation Efectivity in Improving Student Achievement.This study was conducted in 2015. The results of this study concluded that: 1) The fund implementation of the School Operational Grant (BOS)in SMP Negeri 1 Biromaru is effective, because the indicators that lead to the achievement of objective educational goalset SMP much has been achieved, and 2) The effects of BOS Program Implementation Efectivity in Improving Student Achievement SMP Negeri 1 Biromaru in Sigi Regency either in context, input, process, and product fund implementation of BOS.